Using lipidomic fingerprints of common octopus' (Octopus vulgaris) muscle to trace its geographic origin - Gaspar, Luís Carlos Lopes (2022)
In recent decades, the common octopus (Octopus vulgaris) has become one of the most important cephalopods in international fisheries due to its high commercial and gastronomic value. In Mediterranean culture, the octopus is a symbol of traditional cuisine for its exquisite flavor and high nutritional value, namely its richness in long-chain polyunsaturated omega-3 fatty acids. Most consumers consider that knowing the origin of seafood is extremely important, encouraging the development of reliable methods to trace the geographical origin of these highly-value products. Recently, the use of lipidomic tools has opened new opportunities in the traceability of the geographic origin of seafood products. Lipids, as the main constituents of biological membranes and energy reserves, reflect organisms' biochemical composition, which in turn is influenced by their diet and habitat conditions. This study aimed to determine the lipidomic fingerprints in the muscle of O. vulgaris captured along the Iberian Atlantic coast and use these profiles to determine their origin place. Samples of O. vulgaris were acquired in commercially relevant ports for fishing for common octopus on the Atlantic coast of the Iberian Peninsula (Ria de Arousa, Ria de Pontevedra, Peniche, Sesimbra and Santa Luzia). The recorded results allowed to determine that there are no significant differences in total lipid extracts. However, on what concerns phospholipid content, samples from Peniche exhibited significantly lower values. The analysis of the octopus lipidome allowed the identification of more than 300 molecular lipid species and 13 different lipid classes, evidencing that this cephalopod is a rich source of plasmalogens phospholipids, ceramides and long chain polyunsaturated fatty acids. The statistical tools employed allowed to successfully discriminate all five locations. The major contribution to this discrimination is associated to minority molecular lipid species, some of which are characterized by a high degree of unsaturation in their composition. This study opens new perspectives for the use of lipidomic analyses as a tool for the traceability of seafood products.